ANALYSIS OF THE STRUCTURAL INTEGRITY OF A FUEL TANK DUE TO BUCKLING USING THE FINITE ELEMENT METHOD - Hendri Septian; Mustasyar Perkasa (PT Altin Riset Publishing, 2026)
Storage tanks for fuel oil are commonly used in the oil, gas, and petrochemical industries. These tanks typically have thin-walled structures that are susceptible to buckling under excessive pressure. A hydrostatic test is required to determine the structural strength of the tank and to check for any leaks or cracks in the shell course. During the hydrostatic test, special attention must be given to the dewatering process to avoid excessive pressure differences inside and outside the tank that could lead to buckling. In this study, the tank experienced buckling in the shell course due to errors during the dewatering process, resulting in out-of-roundness in the affected shell course that exceeded the API 650 standard, with a maximum deviation of ±25 mm (from 45 m to <75 m). This thesis analyzes the causes of buckling in the tank shell course and provides recommendations for appropriate repairs so that the tank can be put back into service. NDT UT was carried out to ensure that the shell course thickness remains within the acceptable range, and NDT MPI was conducted to confirm the absence of discontinuities in the shell course welds. Based on the actual buckling condition observed in the field, repairs are recommended. For the buckling area, the use of temporary strong backs is suggested. This method is applied for the fit-up of horizontal and vertical joints. In addition, the installation of a stiffening ring is necessary to restore the tank roundness in compliance with API 650 standards. The material used for the stiffening ring is angle steel 100 × 90 × 7t.